2015
DOI: 10.1111/all.12730
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 mediates the house dust mite‐induced release of chemokine ligand CCL20 by airway epithelium

Abstract: Our data show for the first time that ADAM10 activity contributes to HDM-induced shedding of chemokines, including CCL20. The ADAM10/CCL20 axis may be a target for novel therapeutic strategies in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…In addition, our laboratory has demonstrated that the HDM-induced ER stress is linked to increased CCL20 and IL-6 in wild-type mice (23). Furthermore, the proinflammatory cytokines (IL-6), Th2 cytokines (IL-13 and IL-4), Th17 cytokines (IL-17A), and chemokines, including CCL20, KC, and G-CSF, have been shown to play a critical role in the pathogenesis of allergic airway disease (1,7,18,47,48,64). In this study, TUDCA significantly decreased HDMinduced inflammatory cells in BALF and also significantly decreased IL-13, IL-4, IL-17A, IL-6, CCL20, KC, and G-CSF levels in HDM-challenged mice, either during the preventive regimen or rechallenge regimen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, our laboratory has demonstrated that the HDM-induced ER stress is linked to increased CCL20 and IL-6 in wild-type mice (23). Furthermore, the proinflammatory cytokines (IL-6), Th2 cytokines (IL-13 and IL-4), Th17 cytokines (IL-17A), and chemokines, including CCL20, KC, and G-CSF, have been shown to play a critical role in the pathogenesis of allergic airway disease (1,7,18,47,48,64). In this study, TUDCA significantly decreased HDMinduced inflammatory cells in BALF and also significantly decreased IL-13, IL-4, IL-17A, IL-6, CCL20, KC, and G-CSF levels in HDM-challenged mice, either during the preventive regimen or rechallenge regimen.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, any effect of TUDCA on epithelial integrity is likely to protect against the extent of airway smooth muscle activation and thus central airway resistance. Additionally, TUDCA attenuated the HDM-induced increases in the levels of IL-13, IL-4, IL-17A, IL-6, and chemokines that play crucial roles in asthma pathophysiology (1,7,18,(47)(48)(49)64). Henceforth, we speculate that the protective effect of TUDCA on central airway resistance might be mediated through its effect on inflammatory cytokines/chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…The airway epithelium could function as a critical immune regulator through secretion of chemokines, cytokines, growth factors, and antimicrobial peptides. In this regard, the epithelial cells produce IL‐23, IL‐33, and thymic stromal lymphopoietin (TSLP), as well as CC family chemokines, which are regarded as critical epithelial factors to initiate and amplify airway inflammation . These newly identified epithelial‐specific cytokines are produced prior to the release of the more commonly recognized Th2‐type allergic inflammation mediators, including IL‐4, IL‐5, and IL‐13.…”
Section: Introductionmentioning
confidence: 99%
“…Illustratively, ADAM 10 drives T H 2 bias 4 and promotes IgE synthesis by being a CD23 sheddase, 5 an effect incidentally ascribed to Der p 1 itself 3 . In airway epithelial cells, ADAM 10 liberates CCL20 (which recruits dendritic cells and T H 17 cells and promotes mucus hyperplasia), CCL2 (chemoattractant for dendritic cells), CCL5 (eosinophil chemokine), CXCL8 (neutrophil chemokine), and CXCL16 (T-cell chemoattractant) 6, 7. It is also involved in stem cell factor-dependent mast cell migration.…”
mentioning
confidence: 99%